Gold (Xau) Trading Practices Within The Ronss Elite Community On The Metatrader 5 Platform: A Sharia Economic Law Perspective - Amir Aditia Wilujeng; Fetri Fatorina; M. Imron (Jurnal El-Thawalib, 2026)
Gold trading (XAU) is a modern form of trading that has developed alongside advances in digital technology and the use of online trading platforms. The practice of gold trading without the direct delivery of physical gold has sparked debate in Islamic economic law, particularly regarding the validity of contracts, delivery mechanisms, and the potential for elements of gharar and maysir. This study aims to analyze the practice of gold trading (XAU) through the MetaTrader 5 platform carried out by members of the Ronss Elite Community and review it from the perspective of Islamic economic law. The research method used is qualitative research with a normative and empirical juridical approach, through a literature review of muamalah fiqh literature, regulations related to futures trading, and field data collection through observation and interviews with community members. The results of the study show that gold (XAU) trading practices by members of the Ronss Elite Community using the MetaTrader 5 platform began with the creation of demo and real accounts, followed by capital deposits. Gold trading was carried out based on technical and fundamental analysis, as well as discipline in planning, recording transactions, and risk management through stop loss and take profit. MetaTrader 5 provides charts, indicators, and analysis tools to support trading decisions. From a Sharia perspective, the practice of trading XAU gold meets the conditions of a salam contract, with mutual agreement between the parties, legal competence, and a clear subject of the contract. Payments are made in advance, with transparent transactions. Although there is a risk of price uncertainty that can lead to elements of gharar and maysir if speculative, this community manages risk with rational analysis. This practice can be considered a contemporary salam contract or bai‘ maushūf fi al-dzimmah, provided that Sharia principles are adhered to.